Perception of fishers about livelihood developmental interventions by various GOs and NGOs in Indian Sundarbans: A comparative study - Ghosh, Amitava; Dana, S. S.; Sharma, Arpita; Sahu, P. K.; Basu, D.; Goswami, R. (Indian Journal of Fisheries, 2022)
The Sundarbans, an important biodiversity hotspot of India, is home to many fishers and owing to its ecological importance, Government Organisations (GOs) and Non-Governmental Organisations (NGOs) are involved in fisheries development. In the present study, interventions done by selected GOs and NGOs and how these have brought a change in the fishers’ livelihood were assessed using the impact matrix of organisations. Information was collected from 300 respondents from 6 selected blocks employing interview schedule. Respondents were asked to rate their perception of how these interventions brought a change in livelihood assets using a five-point scale. Impact scores were calculated using the weighted average technique and revealed impacts on livelihood improvements. Mann-Whitney U-test was applied to know if there was a difference in perception towards interventions done by GOs and NGOs. The study revealed that interventions like bundh building/renovation, demonstration, housing/road/culvert construction, laboratory cum testing facilities and pond excavation scored higher as part of overall perception whereas, SHGs development accrued highest total score for both GOs and NGOs accumulating five capitals of livelihood. Impact matrix exposed that out of five capitals of livelihood, financial capital had a relatively higher score. Keywords: Fisheries, Government organisations, Livelihood, Non-Governmental organisations, Sundarbans